2016
DOI: 10.1051/matecconf/20166406002
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Efficiency of the Vegetable Waste Used as Substrate for Biogas Production

Abstract: Abstract. Different vegetable waste materials (beetroot leaves, turnip leaves, yellow beans, onion waste), commonly found in Central Poland were tested for estimation of energy efficiency while methane fermentation process. The results showed that the biggest green mass of vegetable waste harvested from field was related to the highest water content. In contrary, the higher methane production from 1 Mg of tested biowaste was obtained in case of the materials with the highest dry mass content (yellow beans and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In this study, we have shown that maize straw can be a valuable substrate for a biogas plant, especially if the material has a higher dry matter content. In this case, the methane productivity (201–207 m 3 /Mg FM in the case of MS78 and MS89) is clearly higher compared to maize silage from whole plants (approximately 105 m 3 /Mg FM), which is the most popular substrate in European biogas plants [46,55,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have shown that maize straw can be a valuable substrate for a biogas plant, especially if the material has a higher dry matter content. In this case, the methane productivity (201–207 m 3 /Mg FM in the case of MS78 and MS89) is clearly higher compared to maize silage from whole plants (approximately 105 m 3 /Mg FM), which is the most popular substrate in European biogas plants [46,55,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the process will be able to run correctly, and energy production will be more stable. The possibility of using waste to produce the agricultural biogas has been recognized in many studies, both our own (Janczak et al, 2016;Kozłowski et al, 2019) and by other authors (Soundararaj Manju and Senophiyah-Mary, 2020). For the biogas production, agricultural biogas plants also utilize wasted food of plant origin, including, i.e., selectively collected unsold vegetables and fruits, market waste, or household residues (Czekała et al, 2016).…”
Section: Introductionmentioning
confidence: 90%
“…From the other hand, the use of stillage as the input for biogas plants can be justified in the case of a stable situation of the domestic ethanol industry and when the installation is located in vicinity of a distillery that generates great quantities of this waste. This would minimize the costs related with transport which might contribute to unfavourable economic stability [80,81]. Additionally, the high amount of potassium in molasses and accordingly in distillery waste, not only contaminates fields when it is used as fertilizer but may also inhibit bacteria involved in the anaerobic digestion.…”
Section: Distillery Wastementioning
confidence: 99%